Formulation and Stability Studies of Chloramphenicol asOphthalmic Eye Drop (Tikrit Journal of Pharmaceutical Sciences, 2023)
TI1e cltloiamphenicol is D+threo (-) 2,2 dichloro-N--hydroxy -a( hydroxyl methyl)-pn.itropbenyl acetamide, a bacterioststic and highly effective antibacterial against gr(+) and gr (-) ocular patbogenic bacteria causing conjunctivitis or corn.ea] ulcers. The ophthalmi.c preparations of chloramphen.icol are produced in different formulation due to its lower stability . Therefore , the present study introduce the know-how for the production of cholramphenicol sterjle ophthalmic solution. The ophthalmic preparations of ch1oramphenicol 0.4% are not produced ir,i Syria as well as the actice agent. Therefore , the prepared report produces the know -bow for the production and study the stability for sterile solution. chloramphenicol for ophlha1mic solution is a sterile, dsy mixture with borax buffer .The active ingredient is chloramphenicol at concentration ( 40mg I ml ) was prepared under aseptic conditions. The fait yellow color ophthalmic so1ution , clear , sterile , isotonic with 306 mOsm / Kg , the pH measured at 6.51. This so1ution did not cause any eye irritation in rabbits after daily application for four consecutive days . Finally , tbe stability of the prepared chloramphenicol 0.4 % eye drops was studied at 4, 25 , 40 and 50C0 for 90 days in glass amber containers and calculated tl1e expiration date of the preparation on was approximately two years